2021
DOI: 10.2147/ott.s296816
|View full text |Cite
|
Sign up to set email alerts
|

Serum Exosomal miRNA-1226 as Potential Biomarker of Pancreatic Ductal Adenocarcinoma

Abstract: Background Pancreatic ductal adenocarcinoma (PDAC) is the fourth leading cause of cancer-related mortality and it is urgent to find biomarkers for early detection of PDAC. Exosomal miRNAs are useful biomarkers for cancer detection. The aims of this study were to investigate the potential role of serum exosomal miRNA in detection of PDAC and to analyze the correlation between the levels of exosome miRNA and the tumor biological behaviors. Materials and Methods Thirteen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 43 publications
(49 reference statements)
0
21
0
Order By: Relevance
“…Although multiple studies are trying to find effective diagnostic markers for Pca, early diagnosis of Pca is still difficult ( 25 ). Several circulating exosomal miRNA biomarkers have been reported for the diagnosis of Pca 19 , including miR-1226 ( 26 ), miR-196a/1246 ( 27 ), miR-191/21/451a ( 28 ), and miR-10b/21/30c/161a/let-7a ( 29 ). However, few studies have investigated the diagnostic value of Exo-miR-19b ( 20 ), and no reports have been performed in Pca.…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple studies are trying to find effective diagnostic markers for Pca, early diagnosis of Pca is still difficult ( 25 ). Several circulating exosomal miRNA biomarkers have been reported for the diagnosis of Pca 19 , including miR-1226 ( 26 ), miR-196a/1246 ( 27 ), miR-191/21/451a ( 28 ), and miR-10b/21/30c/161a/let-7a ( 29 ). However, few studies have investigated the diagnostic value of Exo-miR-19b ( 20 ), and no reports have been performed in Pca.…”
Section: Discussionmentioning
confidence: 99%
“…Yokota and colleagues reported that serum exosomal miR-638 is a prognostic marker of HCC via downregulation of endothelial cell VE-cadherin and ZO-1 [ 15 ]. Moreover, Wang and colleagues suggested that serum exosomal miRNA-1226-3p is a potential biomarker for diagnosing and predicting the tumor invasion or metastases of pancreatic ductal adenocarcinoma [ 16 ]. Furthermore, Shen and colleagues demonstrated that cancer-derived exosomal miR-7641 may serve as a promising noninvasive diagnostic biomarker and potential targetable candidate in breast cancer treatment [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are remarkably stable in body fluids, and they can carry various contents from donor cells to recipient cells, including proteins, lipids, DNA, and RNA [ 13 , 14 ]. Emerging evidence has demonstrated that exosomes and their delivered miRNAs have potential use as novel potential biomarkers in various cancers, such as HCC [ 15 ], pancreatic ductal adenocarcinoma [ 16 ], glioblastoma [ 17 ], prostate cancer [ 18 ], colorectal cancer [ 19 ], and breast cancer [ 20 ]. However, many circulating miRNAs that have been identified as potential diagnostic biomarkers of HCC were not selected through high-throughput screening; thus, other miRNAs that may have a higher diagnostic value were ignored.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to GC, HCC and CRC, miR-149-5p has also been studied in other digestive system cancers, including oral cancer, esophageal cancer and ductal adenocarcinoma of the pancreas (70)(71)(72)(73)(74)(75)(76).…”
Section: Other Cancers Of Digestive Systemmentioning
confidence: 99%
“…Compared with healthy people and patients with benign pancreatic lesions, the expression of miR-149-5p in serum exosome of patients with pancreatic ductal adenocarcinoma (PDAC) was up-regulated (74). But no further studies elucidated the role of miR-149-5p in PDAC, thus to explore the prognostic and diagnostic role of miR-149-5p, more researches should focus on its function in tumor initiation and progression rather than merely examining its expression level.…”
Section: Other Cancers Of Digestive Systemmentioning
confidence: 99%